Karakter Rasa dan pH Yoghurt Susu Kambing pd lama dan Jenis Starter yang Berbeda - Sujono, Sujono; M.R.A, Rofat; K, Hendra; K, Kusnul (Universitas Muhammadiyah Yogyakarta, 2019)
Goat milk is one of the commodities of farming products that is highly nutritious and useful for health. However, goat milk has not been currently preferable due to its smell characteristic. One of the ways in order to make goat milk be able to gain consumers’ interests is by turning it into processed product, such as yoghurt. Yoghurt is a drinking product made as the result of milk fermentation yielded from controlled LAB bacteria. This study is the result of organoleptic assessment, in the form of pH and the flavor of one of PUPPIK skim dedicated products. The flavor organoleptic observation with students as the panelists was using de Garmo analytical hedonic test in order to find the most appropriate treatment and the most favorite flavor based on the consumers’ interests. The pH data and data analysis used ANOVA test. The design of this research was RALF (Rancangan Acak Lengkap pola Faktorial/ Factorial Pattern Completely Randomized Design), which consists of 2 factors: fermentation duration (6, 12, 18, and 24 hours) with the temperature of 37OC and the types of starter bacteria (Streptococcus thermophilus, Lactobacillus bulgaricus and combination). Therefore, there were 12 treatments which were repeated 3 times.The result of de Garmo test observation is that the fermentation duration interaction and types of starter bacteria which is mostly preferred by the panelists is the one which is in 24-hour duration of fermentation using Lactobacillus bulgaricus bacteria, with the highest flavor product score of 1,89 (little sour, not bitter), while in term of pH, there is no difference.